أثر إختلاف أساليب التفاعل ببيئة التعلم الالكتروني التشاركي وآلية تنظيم مشروعات التعلم علي تنمية التحصيل المعرفي والاحتفاظ والدافعية للتعلم لدي طلاب تكنولوجيا التعليم - العكية، أميرة أحمد فؤاد حسن; البرادعي، أشرف محمد محمد (جامعة كفر الشيخ - كلية التربية, 2019)
يهدف البحث الحالي لمعرفة أثر اختلاف أساليب التفاعل الإلكتروني (داخل المجموعات/ داخل ثم بين المجموعات) وآلية تنظيم مشروعات التعلم (منظمة/ غير منظمة) على تنمية التحصيل المعرفي والاحتفاظ بالتعلم والدافعية للتعلم باستخدام بيئة التعلم المقترحة للإذاعة والتسجيلات الصوتية لدي طلاب تكنولوجيا التعليم. ولتحقيق هذا الهدف تم تطبيق بيئة تعلم إلكتروني تشاركي قائم علي مشروعات التعلم علي عينة البحث تكونت من (٨٠) طالب من طلاب الفرقة الأولي بقسم تكنولوجيا التعليم بكلية التربية النوعية جامعة كفر الشيخ، وتم توزيعهم علي أربعة مجموعات رئيسية، مجموعة تدرس بأسلوب التفاعل الإلكتروني التشاركي (داخل المجموعات) وآلية تنظيم مشروعات التعلم (منظمة)، مجموعة تدرس بأسلوب التفاعل الإلكتروني التشاركي (داخل ثم بين المجموعات) وآلية تنظيم مشروعات التعلم (منظمة)، مجموعة تدرس بأسلوب التفاعل الإلكتروني التشاركي (داخل المجموعات) وآلية تنظيم مشروعات التعلم (غير منظمة) ومجموعة تدرس بأسلوب التفاعل الإلكتروني التشاركي (داخل ثم بين المجموعات) وآلية تنظيم مشروعات التعلم (غير منظمة)، وذلك تبعاً لمتغيرات البحث الحالي. وتم تطبيق اختبار تحصيلي بعدي، وإعادة تطبيقه بعد مرور ١٥ يوم لقياس الاحتفاظ بالتعلم، ومقياس الدافعية للتعلم باستخدام بيئة التعلم المقترحة على الطلاب، وأشارت النتائج إلى أن أسلوب التفاعل الإلكتروني التشاركي (داخل ثم بين المجموعات) مع آلية تنظيم مشروعات التعلم (منظمة) تؤدي لزيادة التحصيل المعرفي، الاحتفاظ بالتعلم، زيادة مستوى الدافعية للتعلم باستخدام بيئة التعلم المقترحة.
The current research aims to find out the impact of different methods of electronic interaction (within groups/ then between groups) and the mechanism of organizing learning projects (organized/unorganized) on the development of cognitive achievement and retention of learning and motivation to learn using the proposed learning environment for radio and audio recordings of students of learning technology. To achieve this goal, a participatory e-learning environment based on learning projects was applied to the research sample consisted of (80) students of the first team in the department of education technology at the Faculty of Quality Education University Kafr Al-Sheikh, and they were distributed to four main groups, a group taught in the style of interaction Participatory e-learning (within groups), learning project organization (organized), group taught in the method of participatory electronic interaction (within and then between groups), mechanism of organization of learning projects (organized), group taught in the method of participatory electronic interaction (within groups) and mechanism of organization Learning projects (unorganized) and a group taught in the method of participatory electronic interaction (within and then between groups) and the mechanism of organizing learning projects (unorganized), depending on the current research variables. A post-learning test was applied, reapplied after 15 days to measure learning retention, and a measure of motivation to learn using the proposed learning environment for students, and the results indicated that the method of participatory interaction (within and then between groups) with the mechanism of organizing learning projects (organized) Increase cognitive attainment, retention of learning, increase definability of learning using the proposed learning environment.
Keywords: تكنولوجيا التعليم -- التعلم الإلكتروني التشاركي -- التحصيل المعرفي -- الدافعية للتعلم -- طلبة تكنولوجيا التعليم